Geomarketing: uma análise da distribuição geográfica das instituições de ensino superior - Catunda, Reginauro Luz (2010)
The geomarketing is on a theme very relevant for the location decisions of irms. This paper aims to analyze the spatial distribution of an institution of higher education located in Fortaleza in the light of geomarketing. The segment of higher education is a bottom up process, attracting interest from investment groups and their location decisions on strategic gain. The central question of this study is "What criteria are based on the decisions of spatial / geographic institution of higher education in Fortaleza? "Its main goal is" To examine, in light of geomarketing, the criteria guiding the decisions of spatial / geographic faculty object of study. We have defined the following objectives: identify the location of home and business from current customers of this institution, to identify the demographics of the population living near the institution, to identify factors that interfere with local city positively to college searched, identifying the location of higher education institutions in Fortaleza and its relationship with the proximal research institution. The methodology of the study is based bibliographic theoretical theoretical research, an exploratory documentary and secondary data and a qualitative phase through a field with data collection through a structured interview conducted with the director an institution of higher education located in downtown. It was found that despite the non-use of specific tools for geo-referencing the location decisions of the institution were in line with the precepts of geomarketing. It was concluded that despite this nonuse, the strategic goals of future research institution will have a much more assertive with the use of a tool geomarketing because the college is in the process of expansion and their analysis will be more detailed.